Draft genome sequence of Enterobacter sp. strain EA-1, an electrochemically active microorganism isolated from tropical sediment - Rice, Scott A. (2019)
Enterobacter sp. EA-1 is an electrochemically-active bacterium isolated from tropical sediment in Singapore. Here, the annotated draft genome assembly is reported. Whole genome comparison indicates sp. EA-1, along with a previously sequenced Enterobacter isolate from East Asia, forms a distinct clade within the Enterobacter genus.